The Certificate Programme in Music : a means of broadening access to higher music education studies at the University of Stellenbosch - Lesch, Felicia Sharron Margaret (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMus (Music))--University of Stellenbosch, 2010.